2016
DOI: 10.3201/eid2205.150359
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparumK76TpfcrtGene Mutations and Parasite Population Structure, Haiti, 2006–2009

Abstract: Low genetic diversity and low levels of chloroquine resistance among parasites suggest exogenous origin of reported cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
5
12
0
Order By: Relevance
“…Nevertheless, in previous studies. 26 The samples used were collected from different sites in multiple departments in Haiti, and the results obtained were concordant with those of this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, in previous studies. 26 The samples used were collected from different sites in multiple departments in Haiti, and the results obtained were concordant with those of this study.…”
Section: Discussionsupporting
confidence: 82%
“…During the months after the 2010 earthquake, it was not clear whether the influx of emergency-aid workers from various parts of the world would introduce new parasite populations including CQ-resistant parasites. According to this study, and other reports, 26 the prevalence of CQ-resistant mutations has remained very low or is nonexistent in Haiti. [8][9][10] Of the 108 samples that we tested, there was only a single P. falciparum isolate that carried numerous pfcrt, pfdhps, and pfdhfr mutations associated with drug resistance.…”
Section: Discussionsupporting
confidence: 65%
“…The two studies by Charles and others and Morton and others together contributed results from 1,009 samples that were collected over the consecutive years from 2005 to 2010 from multiple sites. 21 , 22 The analysis for mutations in the pfcrt gene found three of 1,009 (0.3%) samples with chloroquine-resistant haplotypes, of which two could not be unequivocally verified. Additional studies on the population genetics of the parasites revealed that the P. falciparum clones in Haiti are highly related and distinct from other countries.…”
Section: Ensuring Efficacy Of Antimalarial Drugs and Preventive Intermentioning
confidence: 98%
“…falciparum (Pf) is the one and only cause of endemic malaria on Hispaniola (there is a lack other Plasmodium species associated with human infection on the island) and thus elimination efforts are being concentrated on this one organism [4]; 3) chloroquine resistance to P . falciparum is rarely reported in Haiti, despite wide use as the standard of treatment for both Haiti and the Dominican Republic [57]. …”
Section: Introductionmentioning
confidence: 99%